2015
DOI: 10.1590/1677-5449.20140037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inter-rater reliability of subjective and objective criteria for diagnosis of lymphedema in upper and lower limbs

Abstract: BACKGROUND: The diagnosis of lymphedema can be obtained objectively by measurement methods, and also by subjective methods, based on the patient's complaint. OBJECTIVE: To evaluate inter-rater reliability of objective and subjective criteria used for diagnosis of lymphedema and to propose a lymphedema cut-off for differences in volume between affected and control limbs. METHODS: We studied 84 patients who had undergone lymphadenectomy for treatment of cutaneous melanoma. Physical measures were obtained by manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this case reported, the feeling of heaviness was quite expressive, which improved with the use of the compression garment. Based on manual perimetry, it is known that there is a strong correlation between the feeling of heaviness and limb volume increase 12 . The feeling of heaviness is improved when the volume of the limb is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In this case reported, the feeling of heaviness was quite expressive, which improved with the use of the compression garment. Based on manual perimetry, it is known that there is a strong correlation between the feeling of heaviness and limb volume increase 12 . The feeling of heaviness is improved when the volume of the limb is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, after its use, only 11.1% of these patients mentioned the discomfort. Campanholi et al 17 observed good agreement between manual perimetry and subjective evaluation through self-report of heaviness and/or upper limb swelling. When limb perimetry decreases, sensation of heaviness is reduced.…”
mentioning
confidence: 97%